Single‐Entity Heparan Sulfate Glycomimetic Clusters for Therapeutic Applications1. Issue 9 (13th January 2015) - Tyler, Peter C.; Guimond, Scott E.; Turnbull, Jeremy E.; Zubkova, Olga V.
Abstract Heparan sulfate (HS) is a highly sulfated glycosaminoglycan with a variety of critical functions in cell signaling and regulation. HS oligosaccharides can mimic or interfere with HS functions in biological systems; however, their exploitation has been hindered by the complexity of their synthesis. Polyvalent displays of small specific HS structures on dendritic cores offer more accessible constructs with potential advantages as therapeutics, but the synthesis of single‐entity HS polyvalent compounds has not previously been described. Herein we report the synthesis of a novel targeted library of single‐entity glycomimetic clusters capped with varied HS saccharides. They have the ability to mimic longer natural HS saccharides in their inhibition of the Alzheimer's disease (AD) protease BACE‐1. We have identified several single‐entity HS clusters with IC50 values in the low‐nanomolar range. These HS clusters are drug leads for AD and offer a novel framework for the manipulation of heparan sulfate–protein interactions in general.